Juridical Review of the Carrier's Responsibility for the Loss of Goods Sent Through Road Transportation Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation - Saruksuk, Esraini; Hertati Gultom, Meli; Janpatar Simamora (Dinasti Research, 2025)
Road transportation plays a strategic role in supporting national logistics but often faces challenges related to the loss of goods during transit. This study aims to examine the legal liability of carriers under Law Number 22 of 2009 on Road Traffic and Transportation (UU LLAJ) and evaluate legal mechanisms available for service users in resolving disputes over lost goods. The study focuses on the application of civil liability principles and the obstacles encountered in practice.This research employs a normative juridical approach, utilizing secondary data from legislation, legal documents, and scholarly literature. The analysis reveals that Article 193 of UU LLAJ stipulates the carrier's obligation to compensate for lost goods, except in cases of force majeure or third-party negligence. However, practical challenges include difficulties in proving carrier negligence and ambiguities in the extent of legal liability, leading to legal uncertainty for service users.The study recommends strengthening regulations to clarify carrier responsibilities, optimizing dispute resolution mechanisms through the Consumer Dispute Resolution Agency (BPSK), and increasing legal awareness among business operators and consumers. These findings are expected to contribute to the development of a safer, more efficient, and reliable transportation system in Indonesia.